2018
DOI: 10.1101/425199
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cellular senescence is a central response to cytotoxic chemotherapy in high-grade serous ovarian cancer

Abstract: High-grade serous ovarian cancer (HGSOC) commonly responds to initial therapy, but this response is rarely durable. Understanding cell fate decisions taken by HGSOC cells in response to treatment could guide new therapeutic opportunities. Here we find that primary HGSOC cultures undergo therapy-induced senescence (TIS) in response to DNA damage induced by chemotherapy. HGSOC-TIS displays most senescence hallmarks including persistent DNA damage, senescence-associated inflammatory secretome, and selective sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 83 publications
(99 reference statements)
2
13
0
Order By: Relevance
“…S3C), suggesting that targeting IDH1 may lead to a sustained cell cycle arrest and therapeutic response. Our results in addition to others suggest that senescence induction in the cell-type specific context of ovarian cancer may overall be tumorsuppressing (17,19,83). Altogether, we propose that targeting IDH1 may act as a novel pro-senescent therapy for HGSC patients.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…S3C), suggesting that targeting IDH1 may lead to a sustained cell cycle arrest and therapeutic response. Our results in addition to others suggest that senescence induction in the cell-type specific context of ovarian cancer may overall be tumorsuppressing (17,19,83). Altogether, we propose that targeting IDH1 may act as a novel pro-senescent therapy for HGSC patients.…”
Section: Discussionsupporting
confidence: 78%
“…Senescence is considered a tumor suppressive mechanism, and senescence induction is considered a beneficial therapeutic outcome (16,19,81). However, senescence may also promote cancer through the senescence-associated secretory phenotype (SASP), which increases inflammation and alters the surrounding microenvironment milieu (82).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular senescence has been reported to be a central response to cytotoxic chemotherapy in HGSC 25 . Indeed, we observed that a key cellular response of HGSC to CX-5461 plus topotecan is a G2/M cell cycle arrest and a senescence-like phenotype, which occurs through an enhanced nucleolar DDR without DNA resection.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due in part to upregulation of multiple metabolic pathways in ATM-low cancers. The combination induced senescence, a stable cell cycle arrest that is considered a positive patient outcome (46)(47)(48). Together, our results provide rationale for exploration of drugs that modify metabolism as combinatorial therapies with ATM inhibitors.…”
Section: Discussionmentioning
confidence: 67%